Labor Mobility for the Poor : Is it Really Possible? - Luthria, Manjula (World Bank, Washington, DC, 2012)
Despite mounting evidence that supports the pro-poor benefits of migration, it has not been easy to unlock doors into development country labor markets. This is largely because both labor sending and receiving countries are unsure that such programs can be designed or executed in a manner that considers their respective (and often competing) interests. This note offers guidance on how to design and implement scheme that is win-win for both host and source countries.